Smart Wearable for Women Safety - Rogini, S.; Bharathi, A. Divya; Subasree, S. G; Jeyanthi, J.E. (International Journal of Membrane Science and Technology, 2023)
The design of a smart wearable bag that provides security for women is presented in this paper. The GSM Module, Touch Sensor, Emergency Switch, LCD, GPS Module, and Node MCU are all included in the smart bag. Shaking the device initiates the system. Automatic alert messages and alert calls with the location and the circumstances are sent to pre-registered cell phone numbers when an alarming situation is identified.